Profile of Brazilian workers victims of occupational accidents with biological fluids - Fernanda Moura D'Almeida Miranda; Elaine Drehmer de Almeida Cruz; Jorge Cestari Vinícius Félix; Luciana Puchalski Kalinke; Maria de Fátima Mantovani; Leila Maria Mansano Sarquis
ABSTRACT Objective: To characterize the Brazilian workers victims of occupational accidents with biological fluids. Method: Epidemiological and descriptive research, in which 284,877 notifications of the Notifiable Diseases Information System were analyzed between 2007 and 2014. We used Stata 13 for data analysis. Results: The highest incidence density occurred in females with 0.8 cases per 1,000 workers/year (n = 222,042, 77.9%); in the age group of 20 to 24 years old, with 0.6 cases per 1,000 workers/year (n = 64,221, 23.3%); with some high school and some college, with 0.6 cases per 1,000 workers/year (n = 141,275, 49.6%). We found that these accidents occurred among 23 occupational subgroups. For the most part, the workers had an employment relationship and had issued the Occupational Accident Notification. Conclusion: It is necessary to rethink the measures of orientation to workers regarding the risks and relative prophylaxis for these accidents, with the aim of reducing them.